Penilaian Kesesuaian Lahan Padi dan Jagung di Kecamatan Lewa Tidahu Kabupaten Sumba Timurn Padi dan Jagung di Kecamatan Lewa Tidahu Kabupaten Sumba Timur - Yonce Melyanus Killa (Savana Cendana, 2020)
The District of Lewa Tidahu was one of districts in eastern sumba regency, Province of Nusa Tenggara Timur (NTT). This area was majority farming in dry farming area with the pottentialy developing rice and corn farming. The aim of this study was to discovering the suitability and chacracteristics of the rice and corn farming land in Lewa Tidahu district, eastern sumba regency. This study were threated in January-June, 2019. The analisys method apply in this studyusing Matching and overlay method by extension modelbuilderin software Archview 3.2. The result of sutability analization by overlay farming land characteristics method showed the class of suitability for rice land farming was very suitable (S1) with 21.301 ha (61,99%) large; suitable enough (S2) with 12.859 ha (37,43%) large; and Non-suitable (N) with 199 ha (0,58%) large. The class of suitability for corn land farming showed very suitable (S1) with 7.651 ha (22,26%) large; suitable enough (S2) with 26.507 ha (77,14%) large; and Non-suitable (N) with 201 ha (0,60%) large. The matching result with the grown condition of rice and corn has a mean limiting factor, it were amount od oxygen demand (ao) like drainage and soil deep, erotion hazard (eh) or slope, land farming preparation (lp) or the rocks on the land surface.